2008
DOI: 10.1103/physreve.77.016302
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of structure-function scaling in turbulent Rayleigh-Bénard convection

Abstract: Direct numerical simulation and stereoscopic particle image velocimetry of turbulent convection are used to gather spatial data for the calculation of structure functions. We wish to add to the ongoing discussion in the literature whether temperature acts as an active or passive scalar in turbulent convection, with consequences for structure-function scaling. The simulation results show direct confirmation of the scalings derived by Bolgiano and Obukhov for turbulence with an active scalar for both velocity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 38 publications
9
77
5
Order By: Relevance
“…Numerical simulations, at Ra = 3.5 × 10 7 and Pr about 1, showed that [18] the height-dependent Bolgiano scale, constructed using the energy and thermal dissipation rates averaged over a cross section at different heights, is comparable to the height H at the center and decreases to 0.2H very close to the top and bottom boundaries. Similarly, more recent numerical simulations [19] show that the local Bolgiano scale, constructed using the local energy and thermal dissipation rates measured at each position, is comparable to H except very close to the top and bottom plates of a cylindrical convection cell where it is smaller than 0.1H for Ra = 1 × 10 9 and Pr = 6.4. The K41 and OC scalings (plus intermittency corrections) have indeed been observed experimentally in the central region [20], but until now, the BO scaling expected to hold near the top and bottom plates has not been observed in experiments.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Numerical simulations, at Ra = 3.5 × 10 7 and Pr about 1, showed that [18] the height-dependent Bolgiano scale, constructed using the energy and thermal dissipation rates averaged over a cross section at different heights, is comparable to the height H at the center and decreases to 0.2H very close to the top and bottom boundaries. Similarly, more recent numerical simulations [19] show that the local Bolgiano scale, constructed using the local energy and thermal dissipation rates measured at each position, is comparable to H except very close to the top and bottom plates of a cylindrical convection cell where it is smaller than 0.1H for Ra = 1 × 10 9 and Pr = 6.4. The K41 and OC scalings (plus intermittency corrections) have indeed been observed experimentally in the central region [20], but until now, the BO scaling expected to hold near the top and bottom plates has not been observed in experiments.…”
Section: Introductionmentioning
confidence: 53%
“…However, the scaling behavior, whatever its nature, would hold only in a certain range of r or the corresponding range of τ , which implies that Eqs. (19) and ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the large-scale range, turbulent fluctuations are produced through buoyancy mechanisms and a Bolgiano-Obukhov subrange is expected to take place as suggested by Ching et al (2013). In an intermediate range of scales, the energy content of the large scales flows down towards smaller ones through an inviscid cascade process reproducing the classical Kolmogorov inertial subrange as reported by experiments (Kunnen et al 2008;Ching et al 2013) and numerical simulations (Calzavarini, Toschi & Tripiccione 2002;Kunnen et al 2008;Kaczorowski & Xia 2013). Finally, in the viscosity-dominated range at small scales, turbulent energy is dissipated.…”
Section: The Generalized Yaglom Equationmentioning
confidence: 80%
“…Our convection cell is the same as in [20], except for its placement on a rotating table for this investigation. We repeat the most important characteristics here.…”
mentioning
confidence: 99%